Sensitivity plot of cy:{-(m^2+m)*10^(-4)} - Cycle of money (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This paper is about a non well-established economy, based on money cycle research. This paper is about the comparison of the cycle of money including the escape savings and financial liquidity. It is plausible to extract the appropriate conclusions about savings in an economy when the savings return to the market for investments and consumption and when these savings are omitted and lost from the economy. This happens through the velocity of financial liquidity and the velocity of escape savings. The current study has used the sensitivity plot of the cycle of money. It uses definitions and mathematical determinations by the cycle of money but estimates on the first time presented results of sensitivity plot of cy:{-(m2+m)*10-4} of the cycle of money in a case study scenario. In this case, escape savings are completely identical to the cycle of money.